Utopian glimmers in African climate dystopias by Ayerdhal, Jean-Marc Ligny, Wanuri Kahiu and Nick Wood - (:unkn) unknown (My University, 2023)
This article compares the dystopian universes imagined by Ayerdhal in Demain, une oasis, Jean-Marc Ligny in AquaTM, Nick Wood in Water Must Fall and Wanuri Kahiu in Pumzi. These climate fictions describe African futures marked by apocalyptic variations around desertification and water scarcity. They activate Afropessimistic images to stage dystopian contexts, conducive to the oppression of local populations and the plundering of the continent’s natural resources. Nevertheless, the authors provide in each of these nightmarish futures, perspectives of new worlds carrying utopian hopes. These emerge from local resistance movements that sketch, often through female figures, the promises of a different future : the possibility of alternative, emancipated and ambitious Africas that intend to forge new narratives and original responses to the continent’s demand for a future.
Keywords: African Research